How It Feels to Be Wired In: On the Digital Cyborg Politics of Mental Disability - Ng, Isla (Atlantis)

(untitled) (Mount Saint Vincent University, 2017)
This article explores the ways dominant theories of the online self depend on ableist assumptions about mind and embodiment. By drawing from disability studies critiques of Cyborg Manifesto, I suggest that the oft-romanticized notion of digital hybridity assumes a non-disabled subject, and consequently renders the relationship between mentally disabled people and digital technology problematic.